Identification of Wb123 as an early and specific marker of Wuchereria bancrofti infection. - Joseph Kubofcik; Doran L Fink; Thomas B Nutman (PLoS Neglected Tropical Diseases, 2012)
Background The current antibody tests used for monitoring in lymphatic filariasis (LF) elimination programs suffer from poor specificity because of the considerable geographical overlap with other filarial infections such as Loa loa (Ll), Onchocerca volvulus (Ov), and Mansonella perstans (Mp). Methods Using bioinformatics to assemble into contigs 2048 expressed sequence tags (ESTs) from the L3 infective larvae of W. bancrofti (Wb), these were next assessed for homology to known proteins and nucleotides and to similar assemblies of L3 larval ESTs of B. malayi (Bm - n = 5068), Ov (n = 4166), and Ll (n = 3315). Nineteen potential L3- and Wb- and/or Bm-specific antigens were identified. Sixteen of the 19 antigens could be expressed as fusion proteins with Renilla luciferase (Ruc); these were used in a rapid Luciferase Immunopreciptation System (LIPS) assay. Results One of the 16 expressed antigens (Wb123) was both highly immunogenic and specific for Wb. Using Wb123-based IgG and IgG4 LIPS assays on well-defined sera from normal North Americans and those infected exclusively with intestinal helminths, we could detect all of the Wb-infected individuals (from diverse geographic regions) with 100% sensitivity and 100% specificity. Using sera from exclusively Ll-infected, Ov-infected Mp-infected or Bm-infected subjects as the negative comparator, the sensitivities were between 98-100% and the specificities ranged between 84-100% (for IgG anti-Wb123) and between 98-100% (for IgG4 anti-Wb123). Blinded assessments using panels of sera from various Wb-, Bm- or non-Wb helminth-infected subjects demonstrated equally high degrees of sensitivity and specificity. Significance We have identified a Wb-encoded antigen that can be used both as a rapid, high throughput tool to diagnose individual Wb infections and as a sensitive method for early detection of recrudescent infections in areas of control and for mapping new areas of Wb transmission.